Effect of garlic concentrates on performance of hybrid catfish fingerlings (Heterobranchus longifilis x Clarias gariepinus) - Irabor, A. E.; Ekelemu, J. K.; Ekokotu, P. A.; Nwachi, O. F. (International Journal of Agricultural Technology, 2021)
The growth of hybrid catfish (Heteroclarias) subjected to varying quantity of garlic concentrate introduced into the diet was examined during a period of twelve weeks. Six hundred (600) fingerlings with average initial mean body weight 3.90 ± 0.02 indiscriminately allotted into five (5) treatments with four replicates each of thirty (30) fish sample respectively. The varying amount of garlic concentrate was at 0%, 2%, 4%, 6, and 8% per kg of feed respectively. Parameters considered in this research include feed conversion ratio (FCR), mean weight gain (MWG), total protein consumed (TPC), protein efficiency ratio (PER) and specific growth rate (SGR). All showed statistical resemblance among treatments. Means of weight gain and specific growth rate (SGR) across treatment revealed that treatment 4 were 53.63 ± 0.63 and 3.04 ± 0.06, respectively. The test ingredient showed some level of significance on the feed conversion ratio (FCR) in treatment 2 (2.57 ± 0.03) compared across treatments. Generally, the best is observed for performance in treatment 3 with 4% addition level of garlic concentrate